تخفيض تكاليف إعادة التأهيل لشبكات الصرف الصحي باستخدام المنطق الضبابي - ابراهيم, مازن (Latakia University Journal -Engineering Sciences Series, 2014)
أن شبكات الصرف الصحي وكغيرها من البنى التحتية تتقادم مع تقدم الزمن. فكان على القيمين على إدارة الشبكة المحافظة عليها بإعادة تأهيلها بالشكل الاقتصادي. وهذا يتطلب معرفة ظروفها البنيوية وأدائها الوظيفي بشكل دقيق. إلا أن التقدير الشخصي والتقريبي للخبراء لهذه الظروف والأداء يحرف المعنيين عن الوصول إلى التقدير الدقيق لدرجات إعادة التأهيل اللازمة وبالتالي الكلف المثلى المخصصة لذلك. لذلك تم اقتراح مجموعة من المؤشرات والمعايير التي تعبر عن مستوى أداء الشبكة بنيويا وفنيا وبيئيا. حيث تساعد هذه المؤشرات و المعايير بتحديد الأنابيب التي تحتاج لإعادة التأهيل وفق درجات. إلا أن درجات التقييم للأنابيب تبعا لهذه المؤشرات والمعايير يتم تقديرها من المعلومات المتوفرة عن الطبيعة البنيوية (الإنشائية) والظروف الوظيفية (الفنية) لأنابيب الشبكة. وهذه الدرجات غالبا ما يصعب تحديدها بشكل تقليدي نتيجة الغموض الذي يشوبها بالإضافة إلى الارتياب المرتكب في حال التقييم بالحالة التقليدية. لذلك تم تحويل التقييم لدرجات إعادة التأهيل من الحالة التقليدية إلى الحالة الضبابية وذلك بمساعدة محرك الاستدلال الضبابي. وأخيرا تم التوصل إلى تخفيض تكاليف إعادة التأهيل نتيجة إمكانية التدرج الكبيرة بالتقييم التي يتمتع بها المنطق الضبابي والتي ساهمت إلى حد كبير بزيادة دقة تقدير الأداء البنيوي والوظيفي للشبكة وبالتالي دقة تقدير درجات وتكاليف إعادة التأهيل اللازمة. والتي ساهمت أيضا بالتخفيف من الهدر الناجم عن التقدير الخاطئ بالنقصان أو الزيادة لحالة عيوب الأنبوب والممكن أن يحصل بالتقييم وفق المنطق التقليدي. The urban sewer networks-like other infrastructures- become obsolete with the passage of time. Therefore, the network manager maintains and rehabilitates it economically. This requires accurate information about the structural nature and functional conditions of the network pipes. However, the experts' personal estimation and the approximate structural conditions and functionality of sewage network for rehabilitation prevent decision makers from getting the exact estimate of the rehabilitation degrees and their allocated costs. Therefore, the aim of this research is to propose a set of indicators and criteria that reflect the level of network performance structurally, technically, and environmentally. These indicators and criteria can assist in selecting the pipes required to be rehabilitated according to their levels. However, Piping Class ratings, according to these indicators and criteria, are obtained from the available data about the structural nature and functional conditions of the network pipes. These grades are often difficult to identify traditionally due to its fuzziness, in addition to the doubt in the evaluation of the traditional case. Therefore, depending on the fuzzy inference system, the evaluation of the rehabilitation levels is changed from the traditional case into the fuzzy one. Finally, this work has contributed to reducing the rehabilitation costs because of the possibility of large gradient assessment recognized by fuzzy logic. These results are widely contributed to the enhancement of the accuracy of estimating the structural and functional performance of the network, and increasing the accuracy of piping class ratings and the required rehabilitation costs. This reduces the waste resulting from the wrong estimation (decreasing or increasing) of the tube defects assessed by crisp logic.